The Relationship between BMI, Leg Length, and Leg Muscle Explosive Power with the Motor Skills Ability in Kids Athletics Frog Jump Event among Sixth Grade Students of SDN Jombang II, Jombang District, Jombang Regency. - Alifiansyah Dharma Asram; Siti Nurrochmah (Jurnal Porkes, 2025)
There have not been many studies that comprehensively analyze the combined role of Body Mass Index, leg length, and leg muscle explosive power on this specific ability in elementary school children. This study aims to analyze the relationship between BMI, leg length, and leg muscle explosive power with the movement ability of kids' athletics in the frog jump event. The method used was quantitative correlational with a cross-sectional approach. The sample consisted of 45 sixth-grade students from SDN Jombang II, selected using total sampling technique. Data were collected through anthropometric measurements (weight, height, leg length) and physical tests (standing broad jump and frog jump), then analyzed using Pearson correlation and multiple linear regression. The results showed that, partially, the three variables had a significant positive relationship with frog jumping (r BMI=0.678; r leg length=0.767; r explosive power=0.720). Simultaneously, the three variables had a very strong (R=0.878) and significant relationship, and were able to explain 77.1% of the variance in frog jump ability (R²=0.771). The largest effective contribution was made by leg length (35.51%), followed by explosive power (30.53%), and IMT (11.05%). It was concluded that these three factors together greatly determine frog jump ability, with leg length as the main contributor.